A Novel Event-Triggered Consensus Approach for Generic Linear Multi-Agents Under Heterogeneous Sector-Restricted Input Nonlinearities - Ahmed, Ijaz; Rehan, Muhammad; Iqbal, Naeem; Ahn, Choon Ki (IEEE transactions on network science and engineering, 2023)
This article deals with the event-triggered (ET) consensus of generic linear multi-agent systems (MASs) subject to heterogeneous sector-restricted input nonlinearities over directed graphs. A new multiplicative input uncertainty-based model is derived to contemplate each agents' sector-restricted input nonlinearity. The proposed approach has been considered for an ET consensus of MASs under input nonlinearities to achieve an efficient control bandwidth by decreasing the sampling frequency. A consensus controller design condition with non-identical control gains is developed to ensure exponential stability with the ET mechanism for generic linear MASs with heterogeneous actuators. To the best of our knowledge, this is the first investigation of the consensus of linear MASs with heterogeneous sector-restricted nonlinearties at the control input, representing any continuous-time function bounded between two linear functions. The addition of the ET mechanism has further strengthened our contribution. This study also demonstrates that the designed ET condition under heterogeneous nonlinear inputs for a strongly connected topology can effectively exclude the Zeno behavior. Finally, a simulation example employing six spacecrafts is provided to illustrate the efficacy of the suggested consensus controller.